Upaya Meningkatkan Motivasi Belajar IPA pada Siswa Madrasah Ibtidaiyah As-Salafiyah Bode Lor dengan Fun Science Experiment (FUNEX) - Rifqi, Muhammad; Fetriani, Risma (ABDIKARYA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
BodeLor Village is one of the villages located in the Plumbon sub-district, where the area is located in the western part of Cirebon Regency. In this village there is one of the Madrasah Ibtidaiyah As-Salafiyah Bode Lor schools. One of the subjects taught at the school is Natural Sciences (IPA). Students still find it difficult or not very enthusiastic about learning science. Therefore, this service will carry out activities aimed at increasing motivation to learn science through fun science experiments. There are several stages carried out, namely: 1) Planning stage, 2) Preparation stage, 3) Implementation stage, 4) Closing stage. This research uses a descriptive qualitative research approach. The participants were students of class 6C As-Salafiyah. Based on the findings, children feel happier learning science by doing experiments directly.